Conservation of the Exon-Intron Structure of Long Intergenic Non-Coding RNA Genes in Eutherian Mammals - Diana Chernikova; David Managadze; Galina V. Glazko; Wojciech Makalowski; Igor B. Rogozin (Life, 2016)
The abundance of mammalian long intergenic non-coding RNA (lincRNA) genes is high, yet their functions remain largely unknown. One possible way to study this important question is to use large-scale comparisons of various characteristics of lincRNA with those of protein-coding genes for which a large body of functional information is available. A prominent feature of mammalian protein-coding genes is the high evolutionary conservation of the exon-intron structure. Comparative analysis of putative intron positions in lincRNA genes from various mammalian genomes suggests that some lincRNA introns have been conserved for over 100 million years, thus the primary and/or secondary structure of these molecules is likely to be functionally important.